2003
DOI: 10.1079/bjn2003951
|View full text |Cite
|
Sign up to set email alerts
|

The effect of polyunsaturated fatty acids, including conjugated linoleic acid, on calcium absorption and bone metabolism and composition in young growing rats

Abstract: The effect of polyunsaturated fatty acids (PUFA), in particular conjugated linoleic acid (CLA), on Ca and bone metabolism is unclear. In a 2 £ 2 factorial design study, forty male 4-week-old rats were fed a control diet containing 70 g added fat (soyabean oil (SBO; n-6 PUFArich diet) or menhaden oil -safflower oil (MSO; n-3 PUFA-rich diet))/kg diet with 0 or 10 g CLA/kg for 8 weeks. Ex vivo prostaglandin E 2 biosynthesis by bone organ culture was significantly higher (P,0·001) in rats consuming SBO compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
75
2
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(82 citation statements)
references
References 40 publications
3
75
2
1
Order By: Relevance
“…For example, Li et al (1999) showed that CLA supplementation (10 g/kg diet) of young growing male rats reduced bone mineralization, possibly by reducing the biosynthesis of PGE 2 by bone, while Kelly et al (2003) found no effect of CLA supplementation, at the same dietary level, on markers of bone formation or bone resorption in young growing male rats, despite a reduction in biosynthesis of PGE 2 . Kelly & Cashman (2004) however, report that CLA reduced markers of bone resorption (urinary pyridinium crosslinks) in ovariectomized rats.…”
Section: Conjugated Linoleic Acid and Bone Metabolism L Doyle Et Almentioning
confidence: 99%
See 4 more Smart Citations
“…For example, Li et al (1999) showed that CLA supplementation (10 g/kg diet) of young growing male rats reduced bone mineralization, possibly by reducing the biosynthesis of PGE 2 by bone, while Kelly et al (2003) found no effect of CLA supplementation, at the same dietary level, on markers of bone formation or bone resorption in young growing male rats, despite a reduction in biosynthesis of PGE 2 . Kelly & Cashman (2004) however, report that CLA reduced markers of bone resorption (urinary pyridinium crosslinks) in ovariectomized rats.…”
Section: Conjugated Linoleic Acid and Bone Metabolism L Doyle Et Almentioning
confidence: 99%
“…Watkins et al (1997) found that a dietary source of anhydrous butterfat (a rich natural source of CLA) stimulated the rate of bone formation in young growing chicks. Similarly, the effect of CLA on bone mass, ash or mineral content in studies with experimental animals is also conflicting, with some studies showing an increase with CLA ( (pigs)), while others found no effect (Li et al, 1999;Kelly et al, 2003;Kelly & Cashman, 2004 (rats) and Demaree et al, 2002;Ostrowska et al, 2003 (pigs)). As already mentioned, CLA is a collective term describing a mixture of positional and geometric isomers of linoleic acid, with conjugated double bonds, which may be of cis or trans configuration at positions 9 and 11 or 10 and 12 (Lawson et al, 2001).…”
Section: Conjugated Linoleic Acid and Bone Metabolism L Doyle Et Almentioning
confidence: 99%
See 3 more Smart Citations